Photoelectric effect of hybrid ultraviolet-sensitized phototransistors from an n-type organic semiconductor and an all-inorganic perovskite quantum dot photosensitizer. Issue 48 (2nd December 2021) - Hong, Shao-Huan; Afraj, Shakil N.; Huang, Ping-Yu; Yeh, Yi-Zi; Tung, Shih-Huang; Chen, Ming-Chou; Liu, Cheng-Liang
Abstract : Hybrid ultraviolet sensitized phototransistors utilizing blends of an n-type DTTQ organic semiconductor and a CsPbBr3 perovskite quantum dot (QD) photosensitizer are reported with an excellent photoresponse. Abstract : Low-dimensional all-inorganic perovskite quantum dots (QDs) have been increasingly developed as photo-sensing materials in the field of photodetectors because of their strong light-absorption capability and broad bandgap tunability. Here, solution-processed hybrid phototransistors built by a dithienothiophenoquinoid (DTTQ) n-type organic semiconductor transport channel mixing with a colloidal CsPbBr3 perovskite QD photosensitizer are demonstrated by manipulating the relative volume ratio from 10 : 0 to 9 : 1, 7 : 3, 5 : 5, 3 : 7, 1 : 9, and 0 : 10. This results in a significantly enhanced photodetection performance owing to the advantages of a high UV absorption cross-section based on the perovskite QDs, efficient carrier transport abilities from the DTTQ semiconductor, and the photogating effect between the bulk heterojunction photocarrier transfer interfaces. The optimized DTTQ : QD (3 : 7) hybrid phototransistor achieves a high photoresponsivity ( R ) of 7.1 × 10 5 A W −1, a photosensitivity ( S ) of 1.8 × 10 4, and a photodetectivity ( D ) of 3.6 × 10 13 Jones at 365 nm. Such a solution-based fabrication process using a hybrid approach directly integrated into a sensitized phototransistor potentially holds promising photoelectric applications towards advanced light-stimulated photodetection.